Penerapan Model Pembelajaran Children Learning In Science Untuk Meningkatkan Pemahaman Siswa Kelas IV SD Muhammadiyah Condongcatur Pada Konsep Bumi Dan Alam Semesta - Andi Ulfa Tenri Pada (Universitas Syiah Kuala, 2010)
This research is conducted to reveal : (1) the application of science study strategy with CLIS study model to improve the students’ understanding of earth and universe concept, (2) the science study strategy with CLIS study model to improve the academic attitude of students, (3) the teacher’s and students’ response to science study strategy with CLIS. Method of the research is a Classroom Action Research (CAR), consisting of three cycles. The data were collected using a test, an observation, and an interview. The result of the students’ concept understanding test was processed statistically using “t-Test”. The improvement of student’s understanding was corelated with Pearson Correlation Technique, while the interview and observation were described, then concluded. The result of data analysis indicate that the model of CLIS for universe and earth concept can improve the mastery of concept. In the first cycle action, it is seen that the acquirement of t0 was 9.069; in the second cycle the t value was 4.054; and in the third cycle it was 9.442; which is bigger than tt of only 2.025. It indicates that CLIS study method has improved the students’ concept understanding in every cycle. The correlation result of the first cycle indicates that the value of r is - 0.273; in the second cycle, the value of r was equal to 0.222. While in the third cycle, the value of r is 0.000. It indicates that the CLIS model study does not influence the improvement of the students’ academic attitude. This study model requires much longer time than study method usually used by the teacher, but the students are happy to study with CLIS study model.